SOME DIFFICULTIES FACED BY THE STUDENTS IN LEARNING PRESENT PERFECT TENSE - Mar’atus Sholeha; Edi Ardian; Samsul Amri (J-Shelves of Indragiri (JSI), 2020)
The research purpose is to know the difficulties faced by the students in learning Present Perfect Tense and the cause of the problems. The design of the research is descriptive research. The number of the population was thirty-six students. The researchers used tests, questionnaires, and interviews to collect the data. After analyzing the data, it found that the average score of test results was 44.67, which was classified as a less classification. Then the ability in using To Be (Has/Have) of present perfect tense was placed in a good rating by the mean score 68.29. Moreover, the students' ability in understanding regular verbs was in a less classification by the mean score 34.03. It also happens for the knowledge in understanding irregular verbs which were classified as less classification by the mean score 39.72. Based on the data obtained from the questionnaires, it shows that most of the students felt that Present Perfect Tense is a problematic material of English. It was proven by seeing that more than 50% of the students said that. It caused by some factors; (1) English materials are less favoured by the students, (2) they are lack of English vocabulary mastery, (3) they have difficulties in recognizing to be of Present Perfect Tense, and (4) they could control the form of verbs changes.